GEOPLANOLOGY MODELING IN THE PLANNING AREA OF MAJALENGKA, WEST JAVA - Nurohim, Dede; Princessca, Channia; Khoirullah, Nur; Sulaksana, Nana; Waliana, Teuku Yan (Faculty of Geological Engineering, Universitas Padjadjaran, 2018)
Based on the geological condition, the study area consisted of carbonate sandstone units (Tmbp), claystone units (Tml), non-carbonate sandstone units (Tpbp), andesitic intrusions (Ia), volcanic breccia units (Qbv), and alluvium (Qal) units. The different types of constituent rocks will affect the innate characteristics or properties of the rock. The regional genetic units explain kinship relations between lithology, morphology, and tectonics. It is used to determine the genetic processes that occur in an area which will later be developed into the smallest units in the geological analysis. In terms of spatial planning, the geological analysis is needed to produce an ideal area in terms of water adequacy, environmental carrying capacity, and disaster. In accordance with Law No. 11 of 2011 concerning the district development plan of Majalengka, then a layout plan emerged that would be applied to the area. Especially in the research area, land suitability covers a possible area that has a value of> 131, spread in the north to the west of the research area, with high to the very high land capability to be developed. The constrained area which has a value of 121-131 is spread in the north to south of the research area, with the ability of the land to be developed. And the limitation area has a value of <121 dominating in the northwest to the southeast of the research area, with low land capacity - very low to be developed. Based on the analysis, there are still some areas that are not in accordance with the pattern of development which should be mainly the development of protected areas.